Penentuan Kadar Karbon Organik pada Sampel Tanah Menggunakan Metode Walkley & Black - Khusnah, Asma’ul; Pawestri, Niken; Utami, Maisari (INDONESIAN JOURNAL OF CHEMICAL RESEARCH, 2025)
Determination of C-organic content in soil using the Walkley & Black method with a UV-Vis spectrophotometer was conducted at the Agricultural Instrument Standards Application Center in Yogyakarta. The samples used in this experiment were soil samples. The analysis method used was the Walkley & Black method with a UV-Vis spectrophotometer. This method works based on the principle of wet oxidation using potassium dichromate (K₂Cr₂O₇) and sulfuric acid (H₂SO₄), where the remaining unreacted dichromate ions are measured using a spectrophotometer at a wavelength of 587 nm. The analysis results showed that the organic C content in the five soil samples ranged from 1.096% to 3.866%, classified from low to high. The variation in organic C content was influenced by environmental factors such as depth, soil texture, and drainage conditions. This analysis is important for determining soil fertility levels and supporting sustainable agricultural land management.